?ANTIPYRETIC AND ANALGESIC ACTIVITY IN CRUDE ETHANOLIC EXTRACT OF CALENDULA OFFICINALIS LINN - Ahmad, Shahna; Qureshi, Shamim; Rehman, Atiq-ur-; Rehman, Zakir-ur-; Badar, Yasmeen (Biological Sciences - PJSIR, 2000)
Crude extractofCalendula officinalis Linn.exhibitedsignificantantipyretic(74.95%inhibition)andanalgesic(27.42% inhibition) effects at a dose of 300 mg kg' 40 mg kg-'respectively as compared to standard i.e. acetyl salicylic acid which exhibited 50.5%and 11.3%respectively.Theextract notonlyreversedtheinduced hyperthermiabut also affect the normothermia in rats. A dose of 20 mgkg' crude extract was found to be equipotent in its analgesic action to 40 mgkg' ofacetyl salicylic acid.The extractwasfoundtobenon-toxic andshowedawidemarginof safetythrough oral route.